Effect of beetroot supplementation on conduit artery blood flow and muscle oxygenation during handgrip exercise - Craig, Jesse Charles (Kansas State University, 2015)
Dietary nitrate supplementation via beetroot juice (BR) has been shown to have positive effects on mitochondrial and muscle efficiency during large muscle mass exercise in humans, and more recently on locomotory muscle blood flow [Q-dot] in rats. To date, an integrated measure of these effects has not been performed in humans. Therefore, we assessed the influence of BR on [Q-dot] and muscle oxygenation characteristics during moderate and severe intensity handgrip exercise. Seven healthy men (age: 25 ± 3 yrs; height: 179 ± 4 cm; weight: 82 ± 9 kg) completed four constant-power exercise tests randomly assigned to condition (BR or placebo (PL)) and intensity (moderate (40% peak) or severe (85% peak)). Resting mean arterial pressure was significantly lower after BR compared to PL (79.3 ± 5.8 vs 86.8 ± 6.7 mmHg; p < 0.01). All subjects were able to sustain 10 min of exercise at moderate intensity in both conditions. BR had no significant effect on exercise tolerance during severe (342 ± 83 vs 382 ± 138 s, p = 0.382). Brachial artery [Q-dot] was not significantly different after BR at rest or any time during exercise in either intensity. Deoxygenated-[hemoglobin + myoglobin] was elevated at min 2 & 3 for moderate (p < 0.05) and throughout severe exercise (p = 0.03) after BR. The estimated metabolic cost ([V-dot]O₂) was not significantly different during either intensity after BR. These findings support the notion that an acute dose of BR may be valuable to reduce blood pressure in young adults, but revealed that it does not augment [Q-dot] or [V-dot]O₂ during small muscle mass handgrip exercise.
Keywords: Beetroot; Blood flow; Oxygenation; Handgrip exercise; Physiology (0719)